Kaj treniram: hokej ali branje? Najbolje kar oboje! - Fras Popović, Sabina (Šolska knjižnica, 2016)
The article presents an example of cooperation between a library and a sport society in developing reading culture, and how a librarian can incorporate the development of reading ability into children's free-time activities; simultaneously, it presents reading as a demanding activity, to which an individual is willing to devote a great deal of time and effort to master it. The purpose of the article is to promote thinking about the possibilities we are offered when shifting the development of reading culture outside of the physical premises of a library or classroom. The example presented has led to the following key findings: children react positively to reading aloud in groups, to the concept of reading as a social event, and to the comparison between training reading and a select sport discipline. It has also been established that children react to reading differently if they see the purpose of it. The results of the presented example can aid school and general librarians, coaches and parents in shaping programmes for cooperation with societies, and in shifting library activities from the established library premises to an individual's living space. The paper has also revealed that parents are a key element. Parents who perceive reading outside of the scope of school requirements as violence against children present a great obstacle to the development of reading culture and reading literacy under non-standard circumstances. This example shows that the problem of (il)literacy and (im)proper reading culture is a systemic problem, one which cannot be solved without involving the family.
Keywords: bralna kultura; bralna pismenost; branje; dečki; hokej; motivacija; sodelovanje; splošne knjižnice; športna društva